Abraham Bar Hiyya on time, history, exile and redemption : an analysis of Megillat ha-Megalleh - Töyrylä, Hannu. (Studies on the Children of Abraham, 2014)
An analysis of Megillat ha-Megalleh by Abraham Bar Hiyya (12th c.) as a complete text in its historical and cultural context, showing that the work - written at a time when Jews increasingly came under Christian influence and dominance - presents a coherent argument for the continuing validity of the Jewish hope for redemption. In his argument, Bar Hiyya presents a view of history, the course of which was planted by God in creation, which runs inevitably towards the future redemption of the Jews. Bar Hiyya uses philosophical, scientific, biblical and astrological material to support his argument, and several times makes use of originally Christian ideas, which he inverts to suit his argument.